EVALUATION OF AIR RADIOACTIVITY MONITORING IN RADIOMETALLURGICAL INSTALLATION - Nofriady Aziz; Septian Hardi Prasetya; Muhammad Afton Muhandis; Zaidi Oktari; Mugiyono Mugiyono; Agus Sunarto (Jurnal Inovasi Teknik Kimia, 2022)
Air radioactivity monitoring was carried out using a continuoust air radioactivity monitoring device, namely the SMARTCAM device, each of which was installed in the chimney of the Radiometallurgical Installation (RMI) Building and then an evaluation of the air radioactivity data was carried out every month during 2020. The purpose of this research about air monitoring was to determine the radioactivity and release from the IRM chimney to the environment during 2020. The data taken are gross alpha (α) and gross beta (β )concentrations at the RMI. The data that has been obtained is then processed to find the daily average value, then the highest average value is taken in one month. The results obtained for each month are then compared with Maximum Permissible Concentration (MPC) for the predetermined gross α and gross β. The results of data evaluation is shown that the air radioactivity monitoring during 2020 at IRM is 0.324 Bq/m3 for alpha and 6.342 Bq/m3 for beta . The amount of air radioactivity of IRM in 2020 when compared to the MPC of 2 Bq/m3 for alpha and 20 Bq/m3 for beta, the air radioactivity is still far below the maximum allowable limit, from these results it can be said that the radioactive gas/aerosol effluent released from the IRM chimney during 2020 did not cause radiological impacts and was safe for the community and the environment around the IRM building.